Synthesis Of Bifunctional Activated Carbon From Gasification Residues For Malachite Green Dye And Atenolol Adsorption - Ahmad, Anis Atikah (2020)
The abundance of gasification char residues which contributed to solid waste management problem is one of the major concerns in biomass gasification industry. This study aims to synthesize activated carbon (AC) derived from gasification residues for malachite green (MG) dye and atenolol (ATN) adsorption via microwave- induced potassium hydroxide (KOH) and carbon dioxide (CO2) activation. Optimum preparation conditions for all ACs prepared were determined using response surface methodology (RSM). Gasified Glyricidia sepium woodchips-based AC (GGSWAC) showed the highest BET surface area and total pore volume of 633.30 m2/g and 0.34 cm3/g, respectively for MG removal; and 483.07 m2/g and 0.26 cm3/g , respectively for ATN adsorption. All adsorbents best fitted to the n-BET isotherm model, suggesting a multilayer adsorption for all systems. Gasified rubber tree root-based AC (GRTRAC) and GGSWAC showed higher maximum saturation capacity (Qe) of 259.49 and 120.57 mg/g, respectively for MG and ATN adsorption at 30ºC. The AC derived from gasified oil palm empty fruit bunches (GOPEFBAC) showed reasonably high removal of MG with Qe value of 219.39 mg/g. Kinetic studies showed that all system followed Avrami model with film diffusion was the rate-limiting step controlling MG removal, while film diffusion and chemisorption controlled the ATN adsorption. Thermodynamic study confirmed that all systems, except ATN-GRTRAC were endothermic in nature. For the column studies, the better correlation of breakthrough data shown by Thomas and Yoon-Nelson model. Results indicated that GGSWAC was the best adsorbent due to its high adsorption performance for both MG dye and ATN removal.